2011
DOI: 10.1167/iovs.10-6643
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-Domain OCT in Multiple Sclerosis Patients: Reproducibility and Ability to Detect Retinal Nerve Fiber Layer Atrophy

Abstract: There are significant differences in RNFL thickness measurements between Cirrus and Spectralis despite a high correlation of measurement between the two instruments. Fourier-domain OCT can be considered a valid device for detecting RNFL atrophy in MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 41 publications
4
55
2
Order By: Relevance
“…Devices with a COV less than 10% are considered highly reliable, while a COV less than 5% indicates very high reliability. 24 To assess the reliability of the repeated measurements, the intraclass correlation coefficients for absolute agreement were calculated. These are used to measure the concordance for continuous variables and correct correlations for systematic bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Devices with a COV less than 10% are considered highly reliable, while a COV less than 5% indicates very high reliability. 24 To assess the reliability of the repeated measurements, the intraclass correlation coefficients for absolute agreement were calculated. These are used to measure the concordance for continuous variables and correct correlations for systematic bias.…”
Section: Discussionmentioning
confidence: 99%
“…The Spectralis OCT is more reliable and more readily detects retinal pathologies than the Cirrus OCT. 24,25 Various reports on Fourier-domain (FD) OCT in healthy and pathologic subjects have been published, 11,23,25 but no studies have evaluated the reliability of FD-OCT measurements on eyes from AD patients or measurements provided by different FD-OCT devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An internal fixation target was used because it is reported to provide the highest reproducibility. 10 The quality of the scans was assessed before the analysis, and poor quality scans were rejected. The Cirrus OCT determines the quality of images using a signal strength measurement that combines signal-to-noise ratio with the uniformity of the signal within a scan and is measured on a scale of 1 to 10, where 1 is categorized as poor image quality and 10 as excellent image quality.…”
Section: Oct Evaluationmentioning
confidence: 99%
“…Numerous studies have analyzed the ability of OCT to detect RNFL thickness abnormalities and changes in the macular area in patients with neurodegenerative diseases, such as multiple sclerosis, in which axonal damage unrelated to inflammatory or autoimmune episodes against myelin occurs already in the early stages of the disease, and axonal neurodegeneration is directly related to permanent functional disability. [7][8][9][10] Recent reports demonstrated decreased retinal thickness in different macular sectors in PD patients compared with healthy subjects, 11,12 and alterations in mean RNFL peripapillary thickness and multifocal electroretinogram have also been observed using timedomain OCT. 5 To our knowledge, spectral-domain OCT has only been used in four previous studies of PD patients, three of which demonstrated a reduction of the macular thickness (inner retinal layer); 11,13,14 only one of these studies showed significant differences in RNFL thickness between PD patients and healthy controls. 15 As these findings might have been influenced by the small sample sizes used, a larger sample would help to corroborate these findings.…”
Section: Introductionmentioning
confidence: 98%